Effects of Resistance Training Combined with Green Tea Treatment on Hyperglycemia and Lipid Profile in Diabetic Rats - E Khosro; F Hovanloo; M Teimoorian; M Saadati; Y Shahvali Koohshoori; H Fallah Huseini (Institue of Medicinal Plants, ACECR, 2016)
Background: Physical exercise and herbal treatment with antioxidant property induce a favorable effect on glucose metabolism in diabetic patients. Objective: The aim of the present study was to investigate the effects of resistance training combined with green tea extract consumption on blood glucose and lipid profile in diabetic rats. Methods: Forty male Wistar diabetic rats aged 5 months and weights 290 ± 20 were divided into 4 groups named as: resistance training, resistance training + green tea, green tea and control. The resistance training and resistance training + green tea groups engaged in exercise for 5 weeks with three times per week moving up the ladder with weight hanging their tail. Green tea extract (100 mg/kg) was gavaged once a day for 5 weeks. Forty eight hours after the last training session and green tea gavages, the fasting blood samples was collected for determination of blood glucose, cholesterol, LDL-C, HDL-C and triglyceride levels. Results: Fasting blood glucose level significantly decreased in all three groups compared with control group, where as triglyceride, cholesterol and LDL-C level significantly decrease in resistance training + green tea group compared to control group. Conclusion: Green tea extract and resistance training improve hyperglycemia and in combination improve lipid profile in diabetic rats.